Building Climate-Resilient Communities; Say No to Migration - Maryam Edalat Moghadam (سیاست نامه علم و فناوری, 2022)
Climate-related disasters triggered displacements of millions of people worldwide. In addition to displacement, the negative consequences of climate change have caused water scarcity, food insecurity, and many other issues such as conflict and political insecurity. Building resilient communities is a key adaptation strategy to combat the impacts of climate change and rely on adaptation policies. Thus, to better withstand the negative impacts of such shocks and recover quickly and strongly from them, countries adopt policies to reduce the vulnerability of individuals and societies. In this paper, the concepts, principles, and perspectives on climate resilience were presented with a descriptive-analytic approach. Then, the experience of various countries, including Iran, on climate resilience by applying indigenous knowledge and technologies to build climate resilience was analyzed. Examining the experiences of different countries shows that some countries have been able to make their societies resilient based on indigenous knowledge and available facilities, while others have been able to invest in education, citizen participation, and infrastructure enhancement. In addition, with the support of the government and private organizations, by applying technology such as early warning systems and artificial intelligence, and relying on self-organization and economic diversity many people have been able to make their living environment resilient and not migrate from their homes. The review shows that Iran's regional experiments on the climate resilience of societies have long been based on indigenous knowledge and that the use of modern technology is not widely used because of poor knowledge of people, high costs, and lack of easy access. Therefore, in order to make the various regions of Iran more resilient, to raise society's awareness of environmental hazards, strengthen infrastructure, integrate indigenous knowledge with technology, and provide resilience policies according to the characteristics of each region reinforce the applied knowledge aspect and experience needed with the technology.